Site fidelity of fish on a rocky intertidal in the south of Portugal - Cano Compaire, Jesus (2022)
The short-term site fidelity of intertidal fish species was studied in a rocky intertidal zone in southern Portugal using visible implant elastomer tagging. Eleven fish species were caught, tagged and released, seven of which were recaptured. The larger tide pool with the highest complexity level and located at a lower position in the shore level did not have recaptures, while in others the individual fish species recaptured rate ranged from 11.1 to 38.9%, suggesting that the shore height is a dominant factor influencing site fidelity. Although the breeding season seems not to be the only explanation for the recapture rate, the higher mean recapture rates of Parablennius sanguinolentus, Lipophrys pholis and Gobius cobitis may be related to the parental behaviour of these species during that period. Site fidelity of juveniles of Scorpaena porcus in tidepools is reported for the first time, showing the importance of this habitat as a nursery ground.